Value-Added Analysis of Used Cooking Oil Recycling as a Base Material for Floor Cleaning Soap: A Case Study of Putra Abadi MSMEs in Pagalaram City, South Sumatra - Pratiwi, Vania Maharani Rizky; Matin, Hashfi Hawali Abdul; Setyono, Prabang (Universitas Diponegoro, 2025)
Used cooking oil disposed directly to the ground by Putra Abadi MSMEs can threaten the surrounding environment. It is necessary to manage used cooking oil by reprocessing it into another form that can be useful, namely by processing it into floor cleaning soap to overcome these problems. The purpose of this study was to determine the suitability of the content of floor cleaning soap made from used cooking oil from the production process of Putra Abadi MSMEs with SNI Floor Cleaning Soap and to determine the added value of floor cleaning soap made from used cooking oil from the production process of Putra Abadi MSMEs in terms of economy and ecology. The method used is the experimental making of floor cleaning soap with analysis of floor cleaning soap content test data referring to SNI 1842: 2019. Analysis of ecological added value is explained descriptively by considering abiotic, biotic, and cultural components; Economic feasibility analysis is carried out by calculating B/C and PBP. The results of this study indicate that variation 4 is the variation with the best composition that meets the SNI 1842: 2019 non-disinfectant category and is economically viable. Manufacturing these products provides ecological benefits, including reducing environmental pollution, restoring aquatic and soil biota habitats, and encouraging sustainable behaviour patterns.